Abdominal infection combined with pneumoperitoneum after renal transplantation: A case report. Issue 5 (3rd February 2023) - Deng, Zhiming; Zhu, Huachen; Du, Wei; Zhang, Hongwei
Abstract : Introduction: Abdominal infection combined with pneumoperitoneum after renal transplantation is rare, clinically confusing, and easily misdiagnosed by physicians as gastrointestinal perforation. Patient concerns: A 54-year-old man experienced abdominal pain and distension together with signs of peritoneal irritation after cadaveric renal transplantation. CT and standing abdominal plain film showed a large pneumoperitoneum in the abdominal cavity and the patient underwent an exploratory laparotomy but no gastrointestinal perforation was found. Diagnosis: No gastrointestinal perforation was found during the operation. In the search for the infectious agent, ascites culture was negative while next-generation sequencing was positive, suggesting the presence of intestinal flora ectopic to abdominal infection with anaerobic respiration fermentation leading to large amounts of gas. Interventions: The patient underwent exploratory laparotomy without gastrointestinal perforation, and then underwent abdominal lavage, placed abdominal drainage tube, and conducted culture and next-generation sequencing examination of ascites. Outcomes: Postoperative symptoms were relieved and intestinal function recovered. After 3 months of outpatient follow-up, the patient had stable transplanted kidney function and was in good spirits and sleeping well, with a good appetite, soft and regular stools, no abdominal pain and distension, and no fever. Conclusion: Patients after kidney transplantation should be wary of abdominal infection being misdiagnosed as gastrointestinal perforation.